The image of the moon in Abdulla Oripov's poems - Umarova Nuriniso Rakhimovna (Zien Journals, 2024)
In this article, one of the leading representatives of Uzbek literature, Abdulla Oripov, published after his death the books “The Moon at Sunset”, “I Miss the Moon”, “The Moon Shines through the Window”, “The Moon” was included in the collection “The Birth of a Poet” in his poems, the moon personified various mental states and experiences.
Keywords: Word; poem; month; childhood